A CRISPR-Cas9 and next-generation sequencing approach for late/very late AcMNPV gene disruption and comprehensive mutation analysis - Chakraborty, Madhuja (University of Waterloo, 2025)
The recent global pandemic COVID-19 has taught us the importance of an efficient biologics manufacturing platform that is cost-effective, reliable, and has high product yield and quality. The baculovirus expression vector system (BEVS) has proven to be a promising platform for the production of recombinant proteins, vaccines, virus-like particles (VLPs), viral vectors, and/or other biologics. In the last two decades, many vaccines and therapeutics manufactured using BEVS have received licenses for animal and human use. The majority of the commercially available BEVS transfer plasmids have foreign genes under the viral polyhedrin (polh) or p10 promoters. Although high gene expression can be achieved with the endogenous baculovirus promoters p10 and polh, they are only active very late in the infection cycle when most of the host cellular machinery is turned off. Significant work has been done to identify native promoters and other regulatory elements with expression profiles higher than polh, as well as promoters weaker than polh to express secretory proteins that require extensive post-translational modifications (PTMs). Certain regions, such as polh, chiA, and v-cath, in the baculovirus genome are not essential for their in vitro replication or foreign protein production in cell culture. Thus, it is possible that if there is an expression of genes not required for progeny virus and/or exogenous protein production in insect cell culture, the resources that are being used for their expression could be ‘an additional burden’, resulting in unnecessary depletion of cellular resources. Identifying and removing these genes would probably divert resources towards the production of foreign proteins and progeny viruses, which could improve the BEVS production platform. Moreover, it was previously demonstrated that there is a ‘competition effect’ among protein-coding genes for cellular resources when Sf9 cells are either coinfected with two monocistronic recombinant baculovirus expression vectors (rBEVs) or infected with a dual-protein producing polycistronic rBEV. This work could point to a direction where competition can arise among baculovirus genes for the use of cellular resources, and the knockout of unnecessary genes could presumably lead to appropriate usage of the resources by the essential genes. Separately, the co-production of rBEVs and recombinant protein products in the supernatant complicates the downstream purification process. Disruption of genes essential for virion formation or production could prevent baculovirus contamination in the culture supernatant, thus reducing the burden on purification processes. In the past, gene disruption or downregulation has been a fruitful strategy to improve the expression of foreign genes in the BEVS. However, the traditional methods used for mutant baculovirus genome generation are time-consuming, labor-intensive, and sometimes also produce wild-type viruses, hence requiring additional purification steps. Not until recently has CRISPR-Cas9 gene editing technology been adapted to the Sf9 insect cells and the baculovirus Autographa californica multiple nucleopolyhedrovirus (AcMNPV). It is believed to be an effective tool to scrutinize baculovirus genes by targeted gene disruption and transcription repression. A systematic study of the late and very late AcMNPV genes using a CRISPR-Cas9-based transfection-infection assay (T-I assay), disrupting the unnecessary sequences, and expressing exogenous gene(s) under a late promoter instead of very late promoters could extend the production time and improve biologics production. Moreover, in the final production stage, targeting AcMNPV genes that are required for progeny virus assembly or release but do not affect foreign protein production could minimize rBEV co-production. In this study, the T-I assay was used to probe late and very late AcMNPV genes for their essentiality. Based on the effect of individual gene disruptions on foreign protein (green fluorescent protein (GFP)) and budded virus (BV) production, 38 targeted AcMNPV genes were categorized as essential (reduced both GFP and BV production) and of special interest (reduced GFP production but did not lower BV production). While we identified 19 AcMNPV genes that are essential for BV production and GFP expression from the late p6.9 promoter, 19 other genes were identified as of special interest whose disruption only reduced GFP expression from the late p6.9 promoter. While phenotypic changes were assessed using the CRISPR-Cas9-based T-I assay, investigating the genomes using whole-genome next-generation sequencing (NGS) revealed further information. First of all, shotgun sequencing was used to generate a consensus sequence of the p6.9GFP rBEV stock used in T-I assays, and this is the first report on whole-genome rBEV sequences to the best of our knowledge. This shotgun-sequenced rBEV served as the reference genome to identify mutations upon CRISPR-Cas9-mediated gene disruptions. We also provided a set of tiled-amplicon primers based on the reference genome and adapted a high-throughput tiled-amplicon sequencing assay to control and targeted rBEV genomes. This sequencing assay, combined with a bioinformatics pipeline for major species, was able to successfully detect mutations within the gp64 gene when gp64 targeting sgRNA was delivered to Sf9-Cas9 cells via a plasmid or rBEV. We further demonstrated that gp64 disruption lowered BV levels without decreasing GFP production, thus reducing BV contamination in cell culture supernatant. To probe the gp64 gene further, we targeted it at six different locations using the T-I assay. Plasmids carrying one or two sgRNA targets were used to evaluate the impact of single and multiple targeting sites on virion and foreign protein production. gp64 disruption with each of these sgRNA targets resulted in decreased infectious and total viral titers, whereas GFP production from the late p6.9 promoter was enhanced or remained similar to the control. Low-frequency genomic changes upon CRISPR-Cas9-mediated gp64 disruptions were successfully assessed by the tiled-amplicon sequencing assay and a variant calling pipeline based on the computational tool iVar. While the iVar tool was originally developed to investigate variants in wild-type virus populations, we adapted it to detect variants in a process system. We also demonstrated that variants can be preserved over viral propagation in cell culture, that is, variants present in the virus stock were also observed in the rBEV genomes recovered from the T-I assay, thus indicating that they are not detrimental to viral fitness.
Keywords: Baculovirus; next-generation sequencing; AcMNPV; CRISPR-Cas9; minimal genome; variant calling pipeline; whole-genome sequencing; bioinformatics